Integrated organizational vigilance and supply chain impacts on the quality of work life: a survey of the views of employees at Ibn Al-Atheer Teaching Hospital for Children - Mayson Abdullah Ahmed Al-Shilma; Bashar Ghanem Hussein Al-Bayati (International Journal of Supply Chain Management, 2020)
Abstract- The current paper aimed at identifying the types of integrated organizational vigilance and supply chain strategy available in the organization under study, which is Ibn Al-Atheer Teaching Hospital for Children. In addition, it intended to clarify the correlation and influence between these types and the quality of work life. It adopted the statistical program (SPSS) to reach the results. The research sample consisted of (50) participants including managers and employees. The questionnaire method was used to demonstrate the correlations and influence between the types of organizational vigilance (represented by technological, environmental, commercial and strategic vigilance) and the dimensions of work life quality (represented by participation in decision-making, stability and job security, wages and salaries, promotion and career advancement). The research problem was to show the impact of organizational vigilance represented by its types on the quality of work life. Accordingly, this study mainly hypothesized that there is a correlation and influence between the organizational vigilance and the quality of work life. Moreover, it assumed that the organizational vigilance represented by its types has an overall impact on the quality of work life. Finally, the research reached a set of findings and recommendations confirming that the organization under study has adopted the research variables.